Human immunodeficiency virus (HIV) infection, sexually transmitted diseases and HIV-antibody testing practices in Belgian prostitutes. Issue 5 (October 1990) - Mak, R; Plum, J; Van Renterghem, L
Abstract : From December 1988 to April 1989, 154 female prostitutes in and around Ghent, Belgium, were interviewed about their knowledge, attitudes and practices in relation to the risks for sexually transmitted diseases (STD) and human immunodeficiency virus (HIV) infection in their profession. Thirty four women worked as window prostitutes, 120 picked up their clients in bars, clubs, and saunas. Blood samples were taken from 123 women. One (0.8%) was seropositive for HIV1, 19 (15.4%) had Hepatitis B core antibodies (anti-HBc), eight (6.4%) showed markers of syphilis. None of them were Hepatitis B surface antigen (HBsAg) carriers. Hepatitis C antibodies (anti-HCV) were present in the serum of three women (2.4%). Overall STD seroprevalence was higher in the group of window prostitutes than in the group of club prostitutes. One woman admitted intravenous drug use. Former testing for anti-HIV antibodies had been performed in 102 (66.5%) respondents, of whom 84 (82.3%) were tested in the year preceding the interview. In 74.5% of the cases, these tests were requested by the women themselves. These results suggest that HIV infection is not yet prevalent in non-intravenous drug using prostitutes in Ghent, but that this situation may change considering their higher rates of past STD. Window prostitutes are at higher risk than club prostitutes. Testing for HIV seems to be common practice, mostly at the request of the women themselves. Health education should discourage the notion of testing as an alternative to using condoms.